Variation in the prevalence, awareness, and control of diabetes in a multiethnic population: A nationwide population study in Malaysia - Rampal, S.; Rampal, L.; Rahmat, R.; Zain, A.M.; Yap, Y.G.; Mohamed, M.; Taha, M. (SAGE Publications, 2010)
The purpose of this study was to determine the association between different ethnic groups and the prevalence, awareness, and control of diabetes in Malaysia. A population-based cross-sectional study using multistage sampling was conducted in Malaysia. Diabetes is defined as having a fasting blood glucose >= 7 mmol/L or a self-reported diabetic on treatment. Among the 7683 respondents aged >= 30 years, the prevalence of diabetes mellitus was 15.2% (95% CI = 14.1, 16.4). Multivariate analysis showed that compared with Malays, Chinese had lower odds (adjusted odds ratio [aOR] 0.71; 95% CI = 0.56, 0.91) and Indians had higher odds of having diabetes (aOR 1.54; 95% CI = 1.20, 1.98). The odds of diabetes increased with age, family history of diabetes, body mass index, and lower education levels. Among those with diabetes mellitus, 45.0% were aware and 42.7% were under treatment. Among treated diabetics, 25.1% had their fasting blood sugar under control. There is a significant association between prevalence of diabetes and different ethnic groups.